(untitled) (Marketing Journal, 2025)
In recent years, the economic relationship between India and Uzbekistan has expanded significantly, shaped by robust diplomatic activity and evolving policy frameworks. This article investigates how official state visits, bilateral working groups, and part icipation in multilateral forums have contributed to this transformation. Notably, the strategic partnership established in 2018 led to concrete agreements in sectors such as trade, education, and infrastructure (Ministry of External Affairs, 2018). Both c ountries have shown increased commitment, with India stepping up its engagement in Central Asia and Uzbekistan pursuing a series of economic reforms to attract foreign investment (Embassy of India, Tashkent, 2023; UNESCAP, 2023). While trade volumes remain relatively modest, the growing footprint of Indian businesses —particularly in pharmaceuticals, IT, and education —points to deeper integration facilitated by diplomacy (EXIM Bank India, 2023; Ministry of Commerce and Industry, 2023). Through qualitative an alysis of government documents, trade data, and sectoral reports, this paper evaluates achievements such as smoother customs protocols and joint ventures, while identifying persisting challenges in areas like financial connectivity and infrastructure. The findings suggest that diplomatic initiatives have evolved from symbolic gestures into tools of substantive economic cooperation, with substantial scope for further growth (UzDaily, 2023; WTO, 2023).